2005
DOI: 10.1017/s0265021503000565
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the pharmacodynamic interaction between remifentanil and propofol by EEG-controlled dosing

Abstract: Within the studied concentration range, remifentanil and propofol showed an additive type of pharmacodynamic interaction on the electroencephalogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The simple additive interaction model accurately reflected the combined effect of propofol and fentanyl on the BIS, which is consistent with the literature findings . The more complex synergistic model was not supported by our data, very likely due to the design limitations.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The simple additive interaction model accurately reflected the combined effect of propofol and fentanyl on the BIS, which is consistent with the literature findings . The more complex synergistic model was not supported by our data, very likely due to the design limitations.…”
Section: Discussionsupporting
confidence: 77%
“…The delay of the anesthetic effect, with respect to plasma concentrations, was described by the effect compartment. The bispectral index (BIS) was linked to the propofol and fentanyl effect‐site concentrations ( C e,P and C e,F ) through an additive E max model : italicBIS=italicBIS0()1EmaxCe,PCe50,P+Ce,FCe50,Fγ()1+Ce,PCe50,P+Ce,FCe50,Fγ where C e50,P and C e50,F denote the concentrations of propofol or fentanyl that produce a half‐maximal decrease in the BIS response, BIS 0 denotes the baseline BIS score (fully awake), E max is the maximal effect fixed to 1 in this study (BIS value of zero at sufficiently high concentrations of propofol or fentanyl) and γ is the Hill coefficient. Inter‐individual variability (IIV) for all PK/PD parameters was modelled assuming log‐normal distribution: Pi=θP0.12emnormalexp0.12em()ηp,i where P i is the set of PK/PD parameters for i th individual, θ P is the population estimate of PK/PD parameters, η P,i is a random effect for a particular parameter with mean 0 and variance ω P 2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, the pharmacokinetic model we used has been demonstrated as adequately accurate in predicting plasma and effect-site concentrations of remifentanil. 7,8 Data from two published studies 16,17 suggested, but did not clearly demonstrate, that the concentrations of remifentanil in the Chinese were lower than that in Caucasians. There is no direct evidence of this because of the differences in methods between the two previous studies and ours.…”
Section: Discussionmentioning
confidence: 98%
“…This is probably related to the very rapid onset of effect the drug (Nieuwenhuijs et al 2003;Habib et al 2002;Dimitriou et al 2006;Lecomte et al 2006;Bilgin et al 2006;Chanavaz et al 2005;Locala et al 2005;Pleym et al 2004;Ouattara et al 2004;Godet et al 2004;Heijmans et al 2004;Joo et al 2004;Unlugenc et al 2003;Jellish et al 2003;Manyam et al 2006;Albertin et al 2006;Mustola et al 2005;Albertin et al 2004;Bouillon et al 2004;Kern et al 2004;Drover et al 2004;Mertens et al 2003;Milne et al 2003;Fechner et al 2003;Criado and Gomez e Segura 2003;Bothtner et al 2002).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Without opioid, the hypnotic concentration required for loss of consciousness is lower than the one to prevent response to noxious stimulations (around 1/3 MAC). It is moderately reduced by low-dose opioids: for example, propofol concentration for loss of consciousness is reduced by 25% in the presence of remifentanil 6 ng/ml (Nieuwenhuijs et al 2003;Manyam et al 2006;Albertin et al 2006;Mustola et al 2005;Albertin et al 2004;Bouillon et al 2004;Kern et al 2004;Drover et al 2004;Mertens et al 2003;Milne et al 2003;Fechner et al 2003;Criado and Gomez e Segura 2003;Bothtner et al 2002). Consequently, at high opioid concentrations the hypnotic needs for loss of consciousness may be higher than those to prevent response to noxious stimuli, and a patient might show no response to surgery and be completely awake, especially if he cannot move to signal his awareness because of neuromuscular blockade.…”
Section: Interactions With Hypnoticsmentioning
confidence: 99%